2021
DOI: 10.1177/09612033211014570
|View full text |Cite
|
Sign up to set email alerts
|

Associations with thrombosis are stronger for antiphosphatidylserine/prothrombin antibodies than for the Sydney criteria antiphospholipid antibody tests in SLE

Abstract: Objectives Antiphosphatidylserine/prothrombin complex antibodies (aPS/PT) are risk factors for thrombosis, yet further validation of their clinical relevance in different ethnic groups is required. We investigated the performance of aPS/PT of IgA/G/M isotypes among Sudanese and Swedish systemic lupus erythematosus (SLE) patients. Methods Consecutive SLE patients/matched controls from Sudan (n = 91/102) and Sweden (n = 332/163) were included. All patients fulfilled the 1982 ACR SLE classification criteria. IgA/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…While association of aPS/PT and venous thrombosis is clear, some have demonstrated no association between aPS/PT IgG/IgM and arterial thrombosis, 48,49 though others did 39,50 . Hoxha et al reported in 2017 that aPS/PT IgG, but not IgM, was more frequently positive in combined arterial and venous thrombosis, compared to arterial or venous thrombosis, although without higher median titers 43 .…”
Section: Discussionmentioning
confidence: 99%
“…While association of aPS/PT and venous thrombosis is clear, some have demonstrated no association between aPS/PT IgG/IgM and arterial thrombosis, 48,49 though others did 39,50 . Hoxha et al reported in 2017 that aPS/PT IgG, but not IgM, was more frequently positive in combined arterial and venous thrombosis, compared to arterial or venous thrombosis, although without higher median titers 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Arterial hypertension was defined as systolic and/or diastolic blood pressure ≥140/90 mmHg or use of antihypertensive medications. Diagnostic methods to establish clinical diagnoses were specified in our previous publication [ 18 ]. The Global APS Score (GAPSS) was calculated for all patients [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of aPS-PT, aCL and anti-β 2 GPI IgA/G/M was performed using the Aptiva system based on a particle-based multi-analyte technology (PMAT; research use only, Inova Diagnostics, San Diego, CA, USA [ 24 ]). Clinical associations for all aPL antibodies among patients were previously published in comparative studies between Sudan and Sweden, using a slightly lower number of Swedish patients ( n = 332) [ 18 , 21 ]. The 99th percentile values of 162 age- and sex-matched population controls were used as cut-offs [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hopkins Lupus Cohort reported that LA was the best predictor of the development of thrombosis in 821 SLE patients [ 24 ]. In an analysis of 332 Swedish SLE patients, LA positivity was the only independent risk factor for venous and arterial thrombosis [ 25 ]. A meta-analysis by Wahl et al also found that patients with SLE and LA had an approximately 3.5-fold increased risk of thrombosis (OR 3.56, 95%CI: 2.01–6.30) (arterial thrombosis OR 3.14, 95%CI: 1.41–6.97, venous thrombosis OR 4.89, 95%CI: 2.25–10.64) [ 26 ].…”
Section: Antiphospholipid Antibodies In Sle Patientsmentioning
confidence: 99%